1982
DOI: 10.1128/aac.22.3.376
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of amikacin and gentamicin by carbenicillin in patients with end-stage renal failure

Abstract: Aminoglycosides are inactivated by carbenicillin in vitro and in patients with end-stage renal failure. In vitro, amikacin is inactivated to a lesser extent than is gentamicin. In five patients on chronic hemodialysis, serum levels of amikacin alone and after repeated intravenous carbenicillin infusions were determined. Analogous gentamicin studies were conducted with five different patients. Neither amikacin serum levels nor serum clearances were affected by carbenicillin. The mean gentamicin serum half-life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 16 publications
(20 reference statements)
0
20
0
Order By: Relevance
“…Pharmacokinetic interactions between j-lactam and aminoglycoside antibiotics have been studied extensively (2,3,10,11,25). Concurrent administration of a penicillin and an aminoglycoside significantly shortens the t1,2 of the latter group of antibiotics (11,19,25), particularly in patients with renal impairment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacokinetic interactions between j-lactam and aminoglycoside antibiotics have been studied extensively (2,3,10,11,25). Concurrent administration of a penicillin and an aminoglycoside significantly shortens the t1,2 of the latter group of antibiotics (11,19,25), particularly in patients with renal impairment.…”
Section: Resultsmentioning
confidence: 99%
“…Chemical inactivation of 1-lactam and aminoglycoside antibiotics occurs in vitro (18). Phamacokinetic interactions between these two classes of antibiotics have been reported in patients with normal and impaired renal functions (3,10,11,14,19,25). Since cefepime, as a 3-lactam, could be used in such a combination therapy, it was deemed * Corresponding author.…”
mentioning
confidence: 99%
“…However, in patients with significant renal failure, subtherapeutic aminoglycoside concentrations and a decreased aminoglycoside elimination half-life during combination therapy with broad-spectrum P-lactam penicillins have been reported (1,18,19). The inactivation of aminoglycosides in patients receiving chronic dialysis therapy has been reported for gentamicin in combination with carbenicillin (1,4,5,19), ticarcillin (4,24), and piperacillin (26). Inactivation of tobramycin given in combination with ticarcillin (18) and carbenicillin (29) has also been described.…”
Section: Materuils and Methodsmentioning
confidence: 99%
“…Reports also indicate that some aminoglycosides are more susceptible to inactivation by these P-lactam antibiotics. Gentamicin and tobramycin have been shown to be inactivated to a greater extent than amikacin or netilmicin (1,9,11). Similarly, some P-lactam antibiotics have a greater propensity to inactivate aminoglycosides.…”
mentioning
confidence: 99%
“…However, prior admixture of aminoglycosides with penicillins will result in the two drugs forming an inactive complex (11,12,(27)(28)(29). The interaction is also thought to occur in vivo (9), but it has been suggested that this has an influence only on an effective available drug for antimicrobial action when the dose of penicillin is very high or the dosage interval of aminoglycoside is prolonged, as in renal failure (4,9,14). In these situations, the combination results in a shortening of half-life.…”
mentioning
confidence: 99%